In vivo anatomical mapping of human locus coeruleus functional connectivity at 3 T MRI. Issue 8 (28th January 2020) - Liebe, Thomas; Kaufmann, Jörn; Li, Meng; Skalej, Martin; Wagner, Gerd; Walter, Martin
Abstract: The locus coeruleus (LC) is involved in numerous crucial brain functions and several disorders like depression and Alzheimer's disease. Recently, the LC resting‐state functional connectivity (rs‐fc) has been investigated in functional MRI by calculating the blood oxygen level–dependent (BOLD) response extracted using Montreal Neurological Institute (MNI) space masks. To corroborate these results, we aimed to investigate the LC rs‐fc at native space by improving the identification of the LC location using a neuromelanin sensitive sequence. Twenty‐five healthy male participants (mean age 24.8 ± 4.2) were examined in a Siemens MAGNETOM Prisma 3 T MRT applying a neuromelanin sensitive T1TSE sequence and functional MRI. We compared the rs‐fc of LC calculated by a MNI‐based approach with extraction of the BOLD signal at the exact individual location of the LC after applying CompCor and field map correction. As a measure of advance, a marked increase of regional homogeneity (ReHo) of time series within LC could be achieved with the subject‐specific approach. Furthermore, the methods differed in the rs‐fc to the right temporoparietal junction, which showed stronger connectivity to the LC in the MNI‐based method. Nevertheless, both methods comparably revealed LC rs‐fc to multiple brain regions including ACC, bilateral thalamus, and cerebellum. Our results are relevant for further research assessing and interpreting LC function, especially in patient populations examined at 3 T MRI.